Determinants of Household Energy Poverty Status in Eastern Indonesia: A Multinomial Logistic Regression Analysis - Tri Lestari; Geffanio Ardasya W. Risqilla; Fansza A. Garin; Jihad Lukis Panjawa; Fitrah Sari Islami (Universitas Muhammadiyah Ponorogo, 2025)
Energy poverty is a complex, multidimensional issue that can hinder sustainable development in many developing nations, including Indonesia. Although the national electrification ratio has improved, gaps in energy access remain, particularly in eastern regions with limited infrastructure. Most prior studies have focused on national trends or developed areas, often relying on single indicators, leaving little detailed analysis for eastern provinces using multidimensional measures and severity levels. This study examines factors influencing household energy poverty in Papua Pegunungan, Papua Tengah, Papua Selatan, and Nusa Tenggara Timur. Data come from the March 2024 Susenas survey, covering 22,989 households. Energy poverty is classified into three levels, and multinomial logistic regression is applied to assess how household characteristics affect the probability of belonging to each level. Findings show that housing size, settlement type (rural/urban), household head’s age, and non-food spending significantly affect energy poverty status. In contrast, education, household size, and household head’s sex have no significant effect. These results point to the need for policies that expand equitable energy infrastructure, improve housing conditions, and ensure affordable, adequate energy access across eastern Indonesia.